Molecular docking studies of bioactive compounds from the leaves of Epiphyllum oxypetalum against Treponema pallidum, Zika virus and liver cirrhosis - R. Abhishek Biswal, P. Jayashree, Kanna Mirunaalini, Vivek Pazhamalai (Journal of Applied Pharmaceutical Science, 2019)
The Epiphyllum oxypetalum is a unique plant that belongs to a cactaceae family. Traditionally, this plant mainly cures sexually transmitted diseases, liver infection, and antiviral disease. The molecular docking analysis was done against virulent bacterial and viral enzymes. The protein responsible for bacterial and viral disease were studied and retrieved from Protein Data Bank. The bioactive compounds of E. oxypetalum were docked against Treponema pallidum, liver cirrhosis, and Zika virus (ZIKV). The result obtained with better binding interactions against T. pallidum was Megastigmatrienone with −5.02Kcal/mol followed by liver cirrhosis was Megastigmatrienone with −4.58Kcal/mol and against ZIKV was Testerone cypionate with −7.84Kcal/mol. Thus, the molecular docking interactions shows better potential of inhibition against virulent enzymes and the bioactive compounds of E. oxypetalum leave which could be used as a lead for treating the diseases, such as Syphilis, liver cirrhosis, and ZIKV.
Keywords: PDB, Treponema pallidum, PDHK2, molecular docking.